Recurrent juvenile psammomatoid ossifying fibroma with secondary aneurysmal bone cyst of the maxilla: a case report and review of literature - Sarode, Sachin C. (Clin Pract, 2018)
Juvenile ossifying fibroma is a benign fibro-osseous lesion commonly affecting the extra-gnathic craniofacial skeleton of the young individuals. The psammomatoid and trabecular variants are its two histopathological subtypes having distinctive clinico-pathological characteristics. Secondary aneurysmal bone cysts are frequently reported to arise in the pre-existing fibro-osseous lesions but rarely reported in the psammmomatoid variant of the juvenile ossifying fibroma. Such hybrid lesions, especially massive in size, tend to exhibit a greater aggressive growth potential and higher recurrence rate and mandate complete surgical removal of the lesion along with a long-term follow-up. The objective of this case report was to present a rare incident of recurrent psammomatoid ossifying fibroma associated with a secondary aneurysmal bone cyst in the maxillary jaw bone of a young patient and review the similar published reports in the English literature.